Implementation of Digital Media In Islamic Religious Education Learning In The Modern Era - Zakkiyah, Ulfatuz; Tanzil, Ahmad Rofiqi; Fuady, Ahmad Silmul; Romlah, Sitti (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
The advancement of digital technology has brought significant transformation to the field of education, including the teaching and learning of Islamic Religious Education (IRE). This study aims to analyze the implementation of digital media in IRE learning in the modern era, focusing on its forms of application, roles, and impact on learning quality. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis is conducted using domain analysis to obtain a comprehensive understanding of digital media usage practices. The findings indicate that digital media such as digital presentations, instructional videos, digital based learning materials, and Learning Management System (LMS) platforms play a crucial role in enhancing students’ motivation, comprehension, and engagement. Digital media enables IRE content to be delivered in a more contextual, interactive, and personalized manner, making the learning process more flexible and adaptive. However, successful implementation requires adequate digital literacy among teachers and students, the availability of technological infrastructure, and proper content supervision to ensure alignment with Islamic values. When managed effectively, digital media serves as a catalyst for transforming IRE learning, supporting the development of students’ knowledge, attitudes, and noble character.